PENGARUH KEBIJAKAN STANDAR PELAYANAN MINIMAL PENGADUAN KONSUMEN DAN SUMBER DAYA MANUSIA TERHADAP KUALITAS PELAYANAN PUBLIK - Salya Purwaganda; Aos Kuswandi (Governance, 2024)
The objectives of this research are: 1. to determine the level of influence for minimum service standard policies on regional mineral water companies tirta patriot in the northern Bekasi district on the quality of public services. 2. to determine the level of influence of human resources in regional mineral water companies tirta patriot in the northern bekasi sub-district towards the quality of public services. 3. to find out the purpose of the influence of the minimum service standard policy and human resources on the regional water company tirta patriot in the northern bekasi sub-district, jointly on the quality of publicservices.Research carried out on regional mineral water companies tirta patriot water for the district in North Bekasi, the results of the study showed that the minimum standard of service was consumer complaints. (x1) influences the regression model y 0,578 so also with human resources (x2) significantly influences the quality of public services (y) with the regression model y 0,304 . 0,578 while based on the test results f, obtained f count for8,791 > f table 3,12 with a significant level . 3,12 because of the probability value < . 8,791that is (3,12 < 8,791) then hypothesis is accepted which means there is influence between the minimum service standard policy variable (x1) and the natural resource variable (x2) together simultaneous quality of public services (y).